Evidence-Based Sports Injury Prevention in the General Population: Effective Programs, Implementation Strategies, and Public Health Policies - Claus André James Valdés; Jose Gregorio Requena Rodriguez; Fabián Patricio Miranda Yáñez; Jorge Roberto Gandarilla San Luis; Blas David Santana Perez; Ángela López García; Eduardo Andres Castillo González (IECCMEXICO, 2026)
Sports and exercise-related injuries represent an important challenge for public health because they may reduce physical activity participation, impair functional capacity, and increase healthcare utilization. This study analyzed the effectiveness of evidence-based sports injury-prevention programs and their potential integration into health-promotion policies for the general population. A structured literature review based on the Scientific Method was conducted using systematic reviews, meta-analyses, randomized controlled trials, consensus statements, and international guidelines. The analysis focused on strength training, neuromuscular exercises, balance and proprioception, structured warm-up programs, training-load management, adherence, implementation, and policy-level strategies. The reviewed evidence showed consistent reductions in injury occurrence with structured exercise-based interventions, with strength training, proprioceptive training, neuromuscular programs, and preventive warm-ups demonstrating particularly favorable outcomes. Higher adherence was associated with greater preventive effectiveness, emphasizing the importance of consistent implementation. Most of the available evidence was concentrated at the individual level, while community, organizational, and policy interventions were less frequently represented. The findings support a multicomponent and multilevel approach in which physical preparation is combined with education, progressive workload management, organizational support, safe environments, and public health strategies. Integrating these measures into schools, fitness centers, recreational sports programs, healthcare services, and community settings may contribute to reducing preventable injuries without limiting participation in physical activity. Sports injury prevention should therefore be incorporated into broader health-promotion policies aimed at creating safer, sustainable, and equitable opportunities for active living.